1989
DOI: 10.1080/00380237.1989.10570547
|View full text |Cite
|
Sign up to set email alerts
|

Replicating Family Size: Does Living in a Single Parent Family Matter?

Abstract: "This paper examines how living in a single parent family affects intergenerational marriage patterns regarding preferred family size. Data collected from 1,300 college students at a large midwestern [U.S.] university provide further evidence of a positive relationship between number of siblings in one's family of origin and preferred marital family size. However, this relationship does not hold for all groups. Factors affecting preferred family size differ for males and females from intact and nonintact f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Despite the reservations that greeted these findings (3) , a degree of "inherited" reproductive behaviour has been observed. Similar work has been done in other countries, all leading to comparable results (Anderton et al, 1987;Johnson and Freymeyer, 1989;Kahn and Anderson, 1992;Murphy and Knudsen, 2002) (4) . In addition to intergenerational transmission of behaviour, it has also been shown that the preferences expressed by children could be explained by their parents' behaviour (Duncan et al, 1965;Stolzenberg and Waite, 1977;Toulemon, 1987) and by their parents' preferences, i.e.…”
supporting
confidence: 73%
“…Despite the reservations that greeted these findings (3) , a degree of "inherited" reproductive behaviour has been observed. Similar work has been done in other countries, all leading to comparable results (Anderton et al, 1987;Johnson and Freymeyer, 1989;Kahn and Anderson, 1992;Murphy and Knudsen, 2002) (4) . In addition to intergenerational transmission of behaviour, it has also been shown that the preferences expressed by children could be explained by their parents' behaviour (Duncan et al, 1965;Stolzenberg and Waite, 1977;Toulemon, 1987) and by their parents' preferences, i.e.…”
supporting
confidence: 73%
“…Heiland, Prskawetz, and Sanderson (2008) discuss three sources of between-person differences in fertility ideals: family background, individual characteristics, and behavioral dispositions. Growing up in a larger family is associated with a higher ideal number of children than growing up in a smaller family (Axinn, Clarkberg, and Thornton 1994;Dey and Wasoff 2010;Gustavus and Nam 1970;Heiland, Prskawetz, and Sanderson 2008;Johnson and Freymeyer 1989). Therefore, family-of-origin experiences can shape schemas of family size (Basten and Gu 2013; Testa and Grilli 2006).…”
Section: Values Resources Attitudes and Fertility Idealsmentioning
confidence: 99%
“…Or in a 1977 supper club fire, employees drew not only on work roles to navigate the fire (e.g. servers helping diners in their area) but also their gender roles—with men providing more overall assistance, especially in attempting to control the fire (Johnston and Johnson, 1989). These roles were enacted in creative ways that enabled, rather than constrained attention by providing employees with a sense of what tasks needed to get done (enhancing the vividness with which they registered the crisis) and specifying how people could relate to each other to fulfill those tasks (enhancing their collective coherence).…”
Section: Theorizing Structure In the Attention-based View Of Crisesmentioning
confidence: 99%